2010
DOI: 10.1017/s0029665110001710
|View full text |Cite
|
Sign up to set email alerts
|

Immune-stimulating effects of lactic acid bacteria in vivo and in vitro

Abstract: The health-promoting effects of lactic acid bacteria (LAB) are well recognised, making them a popular functional food ingredient. Commercially available probiotic products are often promoted as capable of improving immune defences also in healthy subjects. However, while strain-specific differences exist in the effects of LAB, conventional yoghurt bacteria have proved beneficial as well. For comparing the immunological effects of conventional and probiotic LAB, young healthy women received either a commerciall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(48 citation statements)
references
References 20 publications
0
46
0
Order By: Relevance
“…121 A study of college students undergoing the stress of final examinations found a decrease in the relative concentration of lactic acid bacteria in feces after the examination 122 (speciation was not performed). Since lactic acid bacteria have immunomodulating effects 123,124 and may influence the broader composition of the gut microbiome, 125 it seems likely that humans respond to psychosocial stress with responses that are comparable to, if distinct from, the reactions of laboratory animals.…”
Section: Neuroendocrine Mechanismsmentioning
confidence: 99%
“…121 A study of college students undergoing the stress of final examinations found a decrease in the relative concentration of lactic acid bacteria in feces after the examination 122 (speciation was not performed). Since lactic acid bacteria have immunomodulating effects 123,124 and may influence the broader composition of the gut microbiome, 125 it seems likely that humans respond to psychosocial stress with responses that are comparable to, if distinct from, the reactions of laboratory animals.…”
Section: Neuroendocrine Mechanismsmentioning
confidence: 99%
“…However, little is known about the immunomodulatory potential of highly consumed starter bacteria such as dairy propionibacteria. Consumption of fermented products has an impact on immune system function (25), and the bacterial content of these products is responsible for immunomodulation (6,10). Dairy propionibacteria display various probiotic properties either similar to or distinct from those reported for probiotic bifidobacteria and lactic acid bacteria (3).…”
mentioning
confidence: 99%
“…There is evidence suggesting that some probiotics strains can affect the host's immunologic response, stimulating anti-inflammatory cytokines, antioxidants compounds, and generating anti-carcinogenic compounds (25). Thus, probiotics emerge as great alternatives for prevention, and treatment of a variety of gastroenterological conditions, for instance, inflammatory bowel disease, and colorectal cancer (26,27).…”
Section: Introductionmentioning
confidence: 99%